Prove $(A \lor B \rightarrow C) \wedge (C \rightarrow D \wedge C) \wedge (C \rightarrow D) \rightarrow (A \rightarrow D)$ by rules of inference $\:\:$

logicsolution-verification

Task: Prove following with rules of inference (do not use truth table)

$$
(A \vee B \rightarrow C) \wedge (C \rightarrow D \wedge C) \wedge (C \rightarrow D) \rightarrow (A \rightarrow D)
$$

Attempt to prove

  1. $A \vee B \rightarrow C$ (premise)
  2. $C \rightarrow D \wedge C$ (premise)
  3. $C \rightarrow D$ (premise)
  4. $A \vee B \rightarrow D \wedge C$ (Hypothetical syllogism 1,2)
  5. $\neg(A \vee B) \vee (D \wedge C)$ (Logical equivalence 4)
  6. $(\neg A \wedge \neg B)\vee (D \wedge C)$ (Logical equivalence 5)
  7. $\neg A \vee D$ (Add 6)
  8. $A \rightarrow D$ (Logical equivalence)

Q.E.D.


Is my proof valid?

Best Answer

I'm not sure how technical you want to be, but you actually gave the proof for $$A\lor B\to C, C\to D\land C, C\to D \vdash A\to D,$$ not what you showed. You would have to use $\land$-elimination to obtain what you dubbed the "premises" separately. This is the difference between a "proof" (in a metalanguage) and a "true implication".

Have you encountered the symbol $\vdash$ before? If not, don't worry about my point. As long as you only applied the rules you are allowed to apply, then the actual reasoning behind the proof you provided appears to be correct.

(Usually, I take the deduction rules listed here for propositional logic).

Related Question